Differential effects of phenylephrine and norepinephrine on peripheral tissue oxygenation during general anaesthesia: A randomised controlled trial. Issue 8 (August 2015) - Poterman, Marieke; Vos, Jaap Jan; Vereecke, Hugo E.M.; Struys, Michel M.R.F.; Vanoverschelde, Henk; Scheeren, Thomas W.L.; Kalmar, Alain F.
Abstract : BACKGROUND: Phenylephrine and norepinephrine are two vasopressors commonly used to counteract anaesthesia-induced hypotension. Their dissimilar working mechanisms may differentially affect the macro and microcirculation, and ultimately tissue oxygenation. OBJECTIVES: We investigated the differential effect of phenylephrine and norepinephrine on the heart rate (HR), stroke volume (SV), cardiac index (CI), cerebral tissue oxygenation (SctO2 ) and peripheral tissue oxygenation (SptO2 ), and rate-pressure product (RPP). DESIGN: A randomised controlled study. SETTING: Single-centre, University Medical Center Groningen, The Netherlands. PATIENTS: Sixty normovolaemic patients under balanced propofol/remifentanil anaesthesia. INTERVENTIONS: If the mean arterial pressure (MAP) dropped below 80% of the awake state value, phenylephrine (100 μg + 0.5 μg kg −1  min −1 ) or norepinephrine (10 μg + 0.05 μg kg −1  min −1 ) was administered in a randomised fashion. MAIN OUTCOME MEASURES: MAP, HR, SV, CI, SctO2, SptO2 and rate-pressure product (RPP) analysed from 30 s before drug administration until 240 s thereafter. RESULTS: Phenylephrine and norepinephrine caused an equivalent increase in MAP [Δ = 13 (8 to 22) and Δ = 13 (9 to 19) mmHg, respectively] and SV [Δ = 6 ± 6 and Δ = 5 ± 7 ml, respectively], combined with a significant equivalent decrease in HR (both Δ = −8 ± 6 bpm), CI (both Δ = −0.2 ± 0.3 l min −1  m −2 ) and SctO2 and an unchanged RPP (Δ = 345 ± 876 and Δ = 537 ± 1076 mmHg min −1 ). However, SptO2 was slightly but statistically significantly ( P  < 0.05) decreased after norepinephrine [Δ = −3 (−6 to 0)%] but not after phenylephrine administration [Δ = 0 (−1 to 1)%]. In both groups, SptO2 after vasopressor was still higher than the awake value. CONCLUSION: In normovolaemic patients under balanced propofol/remifentanil anaesthesia, phenylephrine and norepinephrine produced similar clinical effects when used to counteract anaesthesia-induced hypotension. After norepinephrine, a fall in peripheral tissue oxygenation was statistically significant, but its magnitude was not clinically relevant.